Perilaku Pencarian Informasi dan Literasi Kesehatan Digital Mahasiswa Universitas Terbuka yang Terpapar Covid-19 - Yasir Riady (IKOMIK: Jurnal Ilmu Komunikasi dan Informasi, 2021)
Digital communication technology plays an important role in succeeding the message of the importance of government health communication and public health authorities during the COVID-19 pandemic. Nowadays both the Internet, social media and social networks have become an important source of health-related information about COVID-19 and the development of both the latest information, prevention and if exposed to what to do during isolation or communicating with local COVID-19 task force officers and the surrounding community. In addition, information related to COVID-19 is spreading faster than the coronavirus itself, which interferes with communication efforts related to government health, especially hoax and misguided news. Therefore, digital health literacy is the main competency to make the COVID-19 web-based information and service environment better and prevent misinformation received by the community. This paper tries to review the digital information literacy obtained by Open University students during exposure to covid-19, on whether there are obstacles received by UT students, what information they are looking for, how the search pattern of information and access to information used, and how the student can still attend lectures at the Open University both through webinar tutorials, online tutorials and UAS Take Home Exam despite exposure to covid-19. Teknologi komunikasi digital memainkan peran penting dalam mensukseskan pesan pentingnya komunikasi kesehatan pemerintah dan otoritas kesehatan masyarakat selama pandemi COVID-19. Saat ini baik Internet, sosial media dan sosial network telah menjadi sumber penting informasi terkait kesehatan tentang COVID-19 dan perkembangannya baik informasi terkini, pencegahan dan jika terpapar apa yang harus dilakukan selama isolasi atau pun berkomunikasi dengan petugas satgas COVID-19. Selain itu, informasi terkait COVID-19 menyebar lebih cepat dari virus corona itu sendiri yang mengganggu upaya komunikasi terkait kesehatan pemerintah khususnya berita hoaks. Oleh karena itu, literasi kesehatan digital merupakan kompetensi utama untuk membuat lingkungan informasi dan layanan berbasis web COVID-19 lebih baik dan mencegah misinformasi yang diterima oleh masyarakat. Tulisan ini mencoba mengulas literasi informasi digital yang didapatkan oleh mahasiswa Universitas Terbuka, apakah ada kendala yang diterima oleh mahasiswa UT, informasi apa yang mereka cari, bagaimana pola pencarian inforamasinya dan akses informasi yang digunakan, serta bagaimana mahasiswa tersebut tetap bisa mengikuti perkuliahan di Universitas Terbuka baik melalui tutorial webinar, tutorial online, dan UAS Take Home Exam meskipun terpapar covid-19.